Dimensi Partisi pada Graf Hasil Operasi Korona Tingkat-k - Amalia, Rica; Ummi Nur Yatun Hasanah; Faisol; Tony Yulianto; Kuzairi (Contemporary Mathematics and Applications (ConMathA), 2024)
Graph theory is one of the subjects in Discrete Mathematics that have long been known and are widely applied in various fields. The topics that are often discussed in graph theory include labeling, coloring, chromatic numbers, metric dimensions, and partition dimensions. Partition dimensions are obtained by grouping all the vertices on the graph into a number of partition classes, then determine the distance of all vertices to each partition class to get a representation. Partition class which representations have different coordinate vectors is called resolving partition. The minimum cardinality of resolving partition is called partition dimensions of the graph. The purpose of this study is to determine the partition dimensions of level corona operation graphs which are GÊ˜kPm, GÊ˜kCm and GÊ˜kKm, where G, Pm, Cm and Km are connected non trivial graph, path graph, circle graph and complete graph respectively, and any integer kâ‰¥1.